The Effect Of Environmental, Social, And Governence (Esg) Performance And Profitability On Firm Value With Firm Size As A Moderating Variable - Monita B, Cantika; Hermuningsih, Sri; Rinofah, Risal (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study examines the influence of Environmental, Social, and Governance (ESG) performance and profitability on firm value, with firm size as a moderating variable, in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The study employs a quantitative approach using secondary data obtained from annual financial reports and sustainability reports. The sample consists of 28 companies selected through purposive sampling. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with the assistance of SPSS version 27. The empirical findings show that ESG performance does not have a significant direct effect on firm value, while profitability has a positive and significant effect on firm value. Firm size does not directly affect firm value, but it plays a moderating role in the relationship between ESG performance and firm value as well as between profitability and firm value. Firm size weakens the relationship between ESG performance and firm value, yet strengthens the relationship between profitability and firm value. Simultaneously, ESG performance, profitability, and firm size significantly influence firm value.